THE EFFECT OF SELF-EFFICACY OF SHIPPING POLYTECHNIC EDUCATION PERSONNEL IN IMPROVING PERFORMANCE - Yulianto, Andri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The objectives of this research are (1) to analyze how much influence leadership has on the performance of Shipping Polytechnic employees through self-efficacy, (2) analyze how big the influence of organizational learning is on the performance of Shipping Polytechnic employees through self-efficacy, and (3) analyze how big the influence of organizational culture on the performance of Shipping Polytechnic employees through self-efficacy. This research uses a multivariate Structural Equation Model (SEM) technique. The software used to process this data is AMOS 22 and the SPSS program as a descriptive statistical measurement tool. The results of this research are (1) Things that can be paid attention to include one dimension of leadership, namely "influencing power" and the dimension of self-efficacy, namely "completing tasks". To improve performance, leaders can combine power in influencing subordinates at work and leaders can help employees in completing tasks. (2) The organizational learning dimension that has the highest value is "Share Vision", this can be combined with the self-efficacy dimension, namely "completing tasks". To improve employee performance at the Banten Shipping Polytechnic and Barombong Shipping Polytechnic, you can use these two approaches by paying more attention to the division of vision in practice in the field. (3) To improve employee performance, leaders can pay attention to the dimension of "shared norms" combined with "completing tasks" to help facilitate every employee activity in the workplace. It is necessary to form and apply general norms that have previously been mutually agreed upon.